Nowcasting risk of poverty and low work intensity in Europe - Olga Rastrigina; Chrysa Leventi; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2015)
Very low work intensity and at-risk-of-poverty are two of the three indicators used for monitoring progress towards the Europe 2020 poverty and social exclusion reduction target. Their timeliness is critical for tracing the effectiveness of policy interventions towards reaching this target. However, due in part to the complicated nature of microdata collection and processing, official Eurostat estimates of these indicators become available with a significant delay. This paper presents a method of estimating ('nowcasting') very low work intensity and poverty risk using the tax-benefit microsimulation model EUROMOD based on EU-SILC data and combined with up-to-date macro-level statistics from the Labour Force Survey. The method is applied to 12 EU Member States for the period 2009-2013. Its performance is assessed by comparing the EUROMOD estimates with the official Eurostat statistics for the years for which the latter are available. The most important measurement issues of the work intensity indicator that are relevant in the context of nowcasting are also discussed.
Keywords: C81; H55; I3; 330; nowcasting; low work intensity; at-risk-of-poverty; European Union; microsimulation